The Ngabungbang Cultural Festival as a Tourist Attraction in Cimande Village, Bogor Regency - Ika Suryono Djunaid; Meylin Stevani Lumiwu (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: The purpose of this research is to study the history of the Ngabungbang  tradition festival, the development of this tradition, and the emerging effects of the Ngabungbang  festival as a cultural tourism attraction in Cimande. Method: This study used a qualitative descriptive method through in-depth interviews with several participants, using a functionalist anthropology approach because it tries to understand traditional values related to local customs and their interrelationships as one of the tourist attractions in Cimande village. Results: The conclusion from this investigation is that the Ngabungbang  tradition is part of the cultural heritage of the Cimande people, this tradition has been practiced for decades starting in the 1930s. During the Ngabungbang tradition procession, there are several traditional activities ahead of the visit to the Kasepuhan Cimande tomb. Furthermore, there are three effects of the Ngabungbang  festival activities as a cultural tourism attraction for Cimande Village residents, namely economic effects, religious effects, and social effects. Contribution: The results of this study are expected to provide information about the history of the Nkumpulbang festival and then the importance of maintaining the original cultural values of the Ngabungbang  festival as a tourist attraction that can have a positive impact on the residents of Cimande Village, such as economic impacts, religious impacts, and social impacts.